ưsing improved Non Ri -Maprec assay to detect virulence mutations in poliomyelitis Vaccine viruses: advantages over rctA0 test - Hoai Anh, Thieu Thi; Luan, Le Thi (VNU Journal of Science: Natural Sciences and Technology, 2007)
Abstract